Technical and Vocational Education and Training and Production of Productive Workforce Graduates: An Incubation Role of Private Sector; A case of selected NACTVET Colleges in Mbeya, Tanzania - Kaula Stephen (Journal of General Education and Humanities, 2022)
This study examines the effects of TVET on producing a productive workforce who are graduates under the moderation role of the private sector. The study was conducted following cases of many graduates completing middle technical and vocational colleges to find they are not employable. To uncover this gap, the study used quantitative research approaches. While the research design was explanatory, the sampling technique was simple random sampling. From a population of 3 NACTVET colleges comprising 3350 units of inquiry, including students, graduates, and tutors from such selected NACTVET colleges, 357 respondents were deduced. Data collection from the sample obtained used a survey questionnaire. Before actual data analysis, a pilot survey, data cleaning, and factor analysis were conducted. Structural equation modeling was used in the actual data analysis. It gives that result Cognitive domain attributes were found to have a positive and insignificant effect on producing a productive workforce of graduates. Also, TVET psychomotor domain attributes were revealed to have positive but insignificant effects on producing productive workforce graduates, and the same results were with behavioral, affective domain skills on producing productive workforce graduates. Moreover, the analysis found positive and significant effects of three factors on producing productive workforce graduates under the moderation role of the private sector. This either suggests to education stakeholders, policymakers, and curriculum developers to adopt the model this study has introduced by bringing the private sector into TVET programs.